Microscopic Pulmonary Tumour Embolism: An Unusual Presentation of Thymic Carcinoma - Brita L Sperling; Donald W Cockcroft; Rajni Chibbar (Canadian Respiratory Journal)
The present report describes the first reported case of microscopic pulmonary tumour embolism (MPTE) from thymic carcinoma. The carcinoma was discovered during an autopsy in a 55-year-old man who had undergone surgery for a pilonidal sinus two weeks before presentation. Pulmonary thromboembolism was suspected. This case was unusual because MPTE has never before been associated with thymic carcinoma, MPTE was the first clinical indication of an occult malignancy, and the clinical presentation was that of sudden onset of dyspnea associated with acute cor pulmonale. The cause of death was determined to be hypoxia secondary to extrinsic compression of the right pulmonary artery and extensive tumour emboli in the small arteries, arterioles and venules of the pulmonary parenchyma. A review of the clinical presentation and diagnosis of MPTE is included.